Effect of Ethical Leadership Development on Improving Business Organizations Within the Context of Organizational Behavior and Turnover Intentions - Dohroo, Mitali; Duggal, Taranjeet; Agrawal, Charul (Prabandhan: Indian Journal of Management, 2023)
Purpose: This study investigated the impact of leadership styles on employee turnover and organizational performance, specifically focusing on ethical leadership and leadership effectiveness. The determinants of employee turnover and their influence on organizational behavior were examined with job stress and turnover intentions. Methodology: In order to gather information on ethical leadership, leadership effectiveness, and employee turnover intentions, questionnaires were delivered to 70 firms in northern India. SPSS and AMOS were used for data analysis. Findings: Ethical leadership and leadership effectiveness significantly affected organizational behavior, specifically regarding job stress and turnover intentions. While ethical leadership had a milder negative impact on turnover intentions and workplace stress, effective leadership had a more pronounced effect. Workplace stress was found to increase turnover intentions substantially, and these intentions were associated with effective leadership and organizational behavior related to work stress. The influence of a leader’s effectiveness and ethical leadership on turnover intentions decreased when accounting for work stress. Effective leadership and ethical practices mitigated work stress and subsequently reduced turnover. Practical Implications: This study underscores the importance of organizational practices and culture that promote ethical behavior among leaders. This strategy improved organizational performance, promoted a positive work environment, increased leadership effectiveness, and decreased attrition rates. Originality: Unlike other research, this study concentrated on Northern India and looked at how leaders’ effectiveness, in combination with their ethical leadership style, affected organizational improvement and turnover intentions.